Growing Pains: The Effect of Common Core State Standards on Perceived Teacher Effectiveness. Issue 1 (2nd January 2016) - Murphy, Audrey Figueroa; Torff, Bruce
Abstract: The recently implemented Common Core State Standards (CCSS) have caused consternation among teachers, making it reasonable to inquire how the standards are affecting teachers' perceptions of their capacity to teach effectively. Survey results indicate that CCSS is indeed reducing teachers' perception of their capacity to teach effectively. The study demonstrates how the simultaneous implementation of standards-based reform and accountability-based reform may produce unfair circumstances for the nation's teachers.